Du désir d’île à l’installation, les circulations migratoires des Métropolitains à la Martinique - Michel Desse (Études Caribéennes)
The migration-West Indies nexus is often dealt with in terms of insular emigration towards Metropolitan France. Indeed, most of the flows are still characterised by a centripetal move that can be accounted for by the hiatus between job supply and the demographic importance of the youth. Nonetheless, Metropolitan-origin mobility exist with West Indian return migration as well as Metropolitan French migration. The boom of the service economy, investments from large French firms and recent advantageous fiscal laws favour this pattern. The article seeks to analyse the new driving forces behind the circular movement between Metropolitan France and Martinique, as well as the economic insertion and the specific territorialities of the new actors.